1970
DOI: 10.3329/bjo.v16i1.5778
|View full text |Cite
|
Sign up to set email alerts
|

Turbinoplasty of hypertrophied inferior turbinate by diode laser

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The operating time ranged from two to twelve minutes. 5,7,8,10,11 Significant improvement was noted by three months time. The reported complications included intraoperative bleeding, postoperative blood mixed nasal secretions, pain, doi: 10.31729/jnma.3644 CC BY doi: 10.31729/jnma.3870 CC BY crusting and synechia.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…The operating time ranged from two to twelve minutes. 5,7,8,10,11 Significant improvement was noted by three months time. The reported complications included intraoperative bleeding, postoperative blood mixed nasal secretions, pain, doi: 10.31729/jnma.3644 CC BY doi: 10.31729/jnma.3870 CC BY crusting and synechia.…”
Section: Introductionmentioning
confidence: 84%
“…The other studies with diode laser have not reported persistent nasal discharge at six months follow up. [6][7][8] Hence, further assessment at six months follow up would have been valuable to assess nasal discharge in our study group. Mucosal oedema and synechiae formation were not observed in any patients postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations